The amazing Maurice and his educated rodents - Pratchett, Terry ([Discworld], 2008)
A talking cat, intelligent rats, and a strange boy cooperate in a Pied Piper scam until they try to con the wrong town and are confronted by a deadly evil rat king. One rat, popping up here and there, squeaking loudly, and taking a bath in the cream, could be a plague all by himself. After a few days of this, it was amazing how glad people were to see the kid with his magical rat pipe. And they were amazing when the rats followed hint out of town. They'd have been really amazed if they'd ever found out that the rats and the piper met up with a cat somewhere outside of town and solemnly counted out the money. The Amazing Maurice runs the perfect Pied Piper scam. This streetwise alley cat knows the value of cold, hard cash and can talk his way into and out of anything. But when Maurice and his cohorts decide to con the town of Bad Blinitz, it will take more than fast talking to survive the danger that awaits. For this is a town where food is scarce and rats are hated, where cellars are lined with deadly traps, and where a terrifying evil lurks beneath the hunger-stricken streets.